Professional stress of special school teachers in Palakkad District - K.V., Radha; Mohana, D. (Gyan Management Journal, 2022)
The present study is aimed to find out the professional stress of special school teachers in Palakkad district, Kerala State. Data were collected from 50 special school teachers dealing students with LD,HI,VI,MR and Autism by administering professional stress scale developed by the researcher and her supervising teacher. Teachers with average stress are 76%where as teachers with severe stress and low stress are 16% and 8% respectively. There is no significant difference in professional stress based on gender, type of management and teaching experience. Among the various components contributing to professional stress, students’ behaviour and parental involvement are more influential than rest of them. The least influential components are working environment and administrative norms. The findings indicate the need to empower special school teachers in the district to deal students and their parents in a most pleasing and diplomatic way. .